If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4x+3)=(5x-22)
We move all terms to the left:
(4x+3)-((5x-22))=0
We get rid of parentheses
4x-((5x-22))+3=0
We calculate terms in parentheses: -((5x-22)), so:We get rid of parentheses
(5x-22)
We get rid of parentheses
5x-22
Back to the equation:
-(5x-22)
4x-5x+22+3=0
We add all the numbers together, and all the variables
-1x+25=0
We move all terms containing x to the left, all other terms to the right
-x=-25
x=-25/-1
x=+25
| r/14+5=4 | | 0.04(x+100)+0.06x=894 | | 24=u+2u | | (8x+4)=(11x-41) | | 13=w-14+2 | | (8x+4)=(11x-41)+180 | | 48=15w-7w | | 2(x-1)/3+3(2x+1)/9=9 | | 3.14.2r=157 | | (8x-7)=(6x+21) | | 364x+576=747x-37 | | 0.15-0.8=1.2v+1.9v | | 0.75-32m=47 | | 0.75+32m=47 | | 128x+36=-52x+3 | | 3/4-5c/12=c/6+7/8 | | 5(2-8r)=10-r | | 2x^-3x+4=0 | | -2n-4n=-24 | | 3/4-5c/12=c/6=7/8 | | -15=1-4n+4 | | 4x^-8x=-4 | | 5(2x+1)=(3x-7) | | K=(67°F+459.67)x5/9, | | 2x^2+24x-128=0 | | 6=19-x | | 6-0.333x=-1 | | -2(x-1)=30 | | 24=x/10-6 | | 3b+b+12=4(b+3) | | 6x+4x+8=2x+20 | | 4(2x+5)=7(x-12) |